2014
DOI: 10.1039/c4dt00908h
|View full text |Cite
|
Sign up to set email alerts
|

Two coordination polymers constructed from a multidentate carboxylic acid ligand with a tertiary amine serve as acid–base catalysts for the synthesis of chloropropene carbonate from CO2 under atmospheric pressure

Abstract: Two new coordination polymers, [Ni(H2O)(Hpdcd)(H2O)2]·DMF (1) and [Co(H2O)(Hpdcd)(H2O)2]·DMF (2) (H3pdcd = 1-(4-carboxyphenyl)-2,5-dimethyl, 1H-pyrrole-3,4-dicarboxylic acid), which were designed based on a tertiary amine ligand, were synthesized and characterized using multiple spectroscopy techniques, including single-crystal X-ray diffraction. These two 1D linear chains possess the properties of both a Lewis acid and organic base, which was confirmed by temperature programmed desorption of ammonia and on-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Moreover, the IR spectra of 1 also confirmed that the structural integrity of 1 was well maintained after the catalytic experiments (Figure S8). A new peak appeared at around 1788 cm –1 , which was ascribed to the new generation of the carbonyl group in cyclic carbonate . Thanks to its high thermal and chemical stability, the recovered 1 could maintain the integrity of the structure after catalysis.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, the IR spectra of 1 also confirmed that the structural integrity of 1 was well maintained after the catalytic experiments (Figure S8). A new peak appeared at around 1788 cm –1 , which was ascribed to the new generation of the carbonyl group in cyclic carbonate . Thanks to its high thermal and chemical stability, the recovered 1 could maintain the integrity of the structure after catalysis.…”
Section: Resultsmentioning
confidence: 97%
“…A number of homogeneous [14][15][16][17][18][19][20] and heterogeneous [21][22][23][24][25][26][27][28][29][30][31] catalysts have been developed for the cycloaddition of CO2 with epoxides. Among them, binary catalytic systems, composed of metal complexes as the catalyst and ammonium salts as the co-catalyst, were found to greatly promote the transformation of CO2 under ambient conditions by the synergy of the Lewis-acidic active sites and Lewis-basic nucleophilic centers [32].…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Using polydentate ligands, which possess multiple N and O donors, has always been a wise choice to construct versatile multinuclear architectures because of their rich coordination patterns, steric effect and electronic effect. [23][24][25][26][27] In this respect, Schiff bases are good candidates and have been widely used in the synthesis of polynuclear complexes due to their good coordination capacity. [28][29][30][31] Owing to their excellent physical, chemical and biological properties, simple synthesis, low cost and versatile applications in various fields, Schiff bases have been quite well studied.…”
Section: Introductionmentioning
confidence: 99%